Certolizumab Pegol Treatment in Three Patients With Takayasu Arteritis - Nuh ATAŞ,; Özkan VARAN,; Hakan BABAOĞLU,; Hasan SATIŞ,; Reyhan BİLİCİ SALMAN,; Abdurrahman TUFAN, (Archives of Rheumatology, 2019)
Although glucocorticoids are the mainstay of treatment in Takayasu arteritis (TA), anti-tumor necrosis factor agents are other treatment options in refractory disease. The onset of TA is generally observed in females of reproductive age. Certolizumab pegol (CZP) lacks a fragment crystallizable region and this gives advantage of minimal transfer through the placenta, which makes CZP a safer option in pregnancy. Although there are case reports and trials about use of infliximab, etanercept, and adalimumab in TA, there are scarce data about use of CZP. In this article, we present three TA cases treated with CZP. While two patients benefited from CZP, one patient was refractory to CZP.